Immunophenotypic characterization of acute leukemia at a public oncology reference center in Maranhão, northeastern Brazil - Noronha, Elda Pereira; Marinho, Heliana Trindade; Thomaz, Erika Bárbara Abreu Fonseca; Silva, Cintia Assunção; Veras, Geni Lourdes Ramos; Oliveira, Raimundo Antônio Gomes (São Paulo Medical Journal, 2011)
CONTEXT AND OBJECTIVES: The incidence of acute leukemia (AL) subtypes varies according to geographical distribution. The aim here was to determine the incidence of morphological and immunophenotypic AL subtypes in the state of Maranhão, Brazil, and to correlate the expression of aberrant phenotypes in children with acute lymphoblastic leukemia (ALL) with prognostic factors. DESIGN AND SETTING: Single prospective cohort study at a public oncology reference center in Maranhão. METHODS: Seventy AL cases were diagnosed between September 2008 and January 2010. For the diagnosis, complete blood cell counts, myelograms (at diagnosis and at the end of the induction phase), cytochemical analysis and immunophenotyping were performed. RESULTS: Among adult patients (n = 22), the incidence of AL types was: ALL (22.7%) and acute myeloid leukemia (AML) (77.3%). The subtype AML M0 occurred most frequently (29.4%). In children (n = 48), the types were: AML (18.7%), most frequently subtype AML M4 (33.4%); biphenotypic acute leukemia (BAL) (4.2%); and ALL (77.1%), including the subtypes B-ALL (72.9%) and T-ALL (27.1%). Among the children with ALL, there were no statistically significant differences between patients with and without aberrant phenotypes, in relation to hematological parameters and treatment response. CONCLUSION: This work demonstrates that the frequencies of AML M0 cases among adults and T-ALL cases among children in Maranhão were high. This suggests that there may be differences in AML subtype incidence, as seen with ALL subtypes, in different regions of Brazil. No association was found between the expression of aberrant phenotypes and prognostic factors, in children with ALL.